Bugging inflammation: role of the gut microbiota - Shen, Sj (Clin Transl Immunology, 2016)
The advent of vaccination and improved hygiene have eliminated many of the deadly infectious pathogens in developed nations. However, the incidences of inflammatory diseases, such as inflammatory bowel disease, asthma, obesity and diabetes are increasing dramatically. Research in the recent decades revealed that it is indeed the lack of early childhood microbial exposure, increase use of antibiotics, as well as increase consumption of processed foods high in carbohydrates and fats, and lacking fibre, which wreak havoc on the proper development of immunity and predispose the host to elevated inflammatory conditions. Although largely unexplored and under-appreciated until recent years, these factors impact significantly on the composition of the gut microbiota (a collection of microorganisms that live within the host mucosal tissue) and inadvertently play intricate and pivotal roles in modulating an appropriate host immune response. The suggestion that shifts in the composition of host microbiota is a risk factor for inflammatory disease raises an exciting opportunity whereby the microbiota may also present as a potential modifiable component or therapeutic target for inflammatory diseases. This review provides insights into the interactions between the microbiota and the immune system, how these affect disease phenotypes, and explore current and emerging therapies that target the gut microbiota as potential treatment for inflammatory diseases.